Operationalizing racialized exposures in historical research on anti-Asian racism and health: a comparison of two methods - Kaniecki, Marie; Novak, Nicole Louise; Gao, Sarah; Harlow, Sioban; Stern, Alexandra Minna (Frontiers in Public Health, 2023)
Background: Addressing contemporary anti-Asian racism and its impacts on health requires understanding its historical roots, including discriminatory restrictions on immigration, citizenship, and land ownership. Archival secondary data such as historical census records provide opportunities to quantitatively analyze structural dynamics that affect the health of Asian immigrants and Asian Americans. Census data overcome weaknesses of other data sources, such as small sample size and aggregation of Asian subgroups. This article explores the strengths and limitations of early twentieth-century census data for understanding Asian Americans and structural racism. Methods: We used California census data from three decennial census spanning 1920-1940 to compare two criteria for identifying Asian Americans: census racial categories and Asian surname lists (Chinese, Indian, Japanese, Korean, and Filipino) that have been validated in contemporary population data. This paper examines the sensitivity and specificity of surname classification compared to census-designated “color or race” at the population level. Results: Surname criteria were found to be highly specific, with each of the five surname lists having a specificity of over 99% for all three census years. The Chinese surname list had the highest sensitivity (ranging from 0.60-0.67 across census years), followed by the Indian (0.54-0.61) and Japanese (0.51-0.62) surname lists. Sensitivity was much lower for Korean (0.40-0.45) and Filipino (0.10-0.21) surnames. With the exception of Indian surnames, the sensitivity values of surname criteria were lower for the 1920-1940 census data than those reported for the 1990 census. The extent of the difference in sensitivity and trends across census years vary by subgroup. Discussion: Surname criteria may have lower sensitivity in detecting Asian subgroups in historical data as opposed to contemporary data as enumeration procedures for Asians have changed across time. We examine how the conflation of race, ethnicity, and nationality in the census could contribute to low sensitivity of surname classification compared to census-designated “color or race”. These results can guide decisions when operationalizing race in the context of specific research questions, thus promoting historical quantitative study of Asian American experiences. Furthermore, these results stress the need to situate measures of race and racism in their specific historical context.